PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN SERTA HARGA TERHADAP LOYALITAS PELANGGAN WARMINDO PADA MAHASISWA SEKOLAH VOKASI UNIVERSITAS GADJAH MADA - Muchammad Vadli Febrian Kusuma; Alexandro Lero Ora; Andrea Michael; Fikri Fajar Ramadhan (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
"WARMINDO" food stall is one of the food businesses that is currently gaining popularity and spreading rapidly everywhere. This can be observed in various crowded locations in major cities. The aim of this study is to analyze the impact of product quality, service quality, and price on customer loyalty towards WARMINDO among Vocational School students at Gadjah Mada University. The research focuses on Vocational School students as the target population. A survey was conducted among 80 students, utilizing questionnaires, and the collected data was processed using probit and logit methods. The test results indicate that in this study, there exists a variable denoted as "Y," which represents the level of interest among Vocational School students at Gadjah Mada University (UGM) towards WARMINDO. Independent variables, including interest level, frequency of student visits to WARMINDO, food prices at WARMINDO, and the quality of service provided, have a positive influence on the loyalty of UGM students. Conversely, variables such as expenditure and satisfaction with food at WARMINDO do not significantly affect the loyalty of Vocational School students at UGM.